Penerapan Analisis SWOT terhadap Pencapaian Target Pembiayaan Mikro Syariah pada BPRS Mitra Agro Usaha di Bandar Lampung - Hasan, Afif Somantri; Ratmono, Ratmono (Universitas Muhammadiyah Metro, 2021)
Talking about the perception of our society about the Bank, we can be sure that the perception that arises is that the Bank is an institution for saving money. The condition in the field states that not all levels of society have made maximum use of bank products. The condition of banking is one of the sectors which is expected to be able to play an active role in supporting national development activities. This role is manifested in its main function as an intermediary institution or intermediary institution between debtors and creditors. Thus, economic actors who need funds to support their activities can be fulfilled and then the wheels of the economy move. The formulation of the problem in this study is